Current Therapeutic Cannabis Controversies and Clinical Trial Design Issues - Russo, Ethan B. (Frontiers in Pharmacology, 2016)
This overview covers a wide range of cannabis topics, initially examining issue in dispensaries and self-administration, plus regulatory requirement for production of cannabis-based medicines, particularly the Food and Drug Administration “Botanical Guidance.” The remainder pertains to various cannabis controversies that certainly require closer examination if the scientific, consumer and governmental stakeholders are ever to reach consensus on safety issues, specifically: whether botanical cannabis displays herbal synergy of its components, pharmacokinetics of cannabis and dose titration, whether cannabis medicines produce cyclo-oxygenase inhibition, cannabis-drug interactions and cytochrome P450 issues, whether cannabis randomized clinical trials are properly blinded, combatting the placebo effect in those trials via new approaches, the drug abuse liability of cannabis-based medicines and their regulatory scheduling, their effects on cognitive function and psychiatric sequelae, immunological effects, cannabis and driving safety, youth usage, issues related to cannabis smoking and vaporization, cannabis concentrates and vape-pens, and laboratory analysis for contamination with bacteria and heavy metals. Finally, the issue of pesticide usage on cannabis crops is addressed. New and disturbing data on pesticide residues in legal cannabis products in Washington State are presented with the observation of an 84.6% contamination rate including potentially neurotoxic and carcinogenic agents. With ongoing developments in legalization of cannabis in medical and recreational settings, numerous scientific, safety and public health issues remain.